The effectiveness of ‘business models’ promoted by the Women in Business project and opportunities for improvement: a report - Goromela, Ezekiel; Urassa, Neema; Omore, Amos O.; Galiè, Alessandra; Jeremiah, Adolf; Mbonea, Magreth; Mtika, Fratern; Chigendi, Neema; Pastory, Conjesta (International Livestock Research Institute, 2022)
The “Women in Business: Chicken Dissemination Project (WiB)” is a three year project implemented by the International Livestock Research Institute (ILRI) in collaboration with partners in Tanzania and Ethiopia. In Tanzania the partners were Tanzania Livestock Research Institute (TALIRI), AKM Glitters and Ministry of Livestock and Fisheries. The project was implemented in Kilimanjaro region in two districts of Siha and Hai and in Lindi region in two districts in Ruangwa and of Lindi in Mtama District Council. The WiB project aimed to develop, promote and test women-led chicken businesses in Ethiopia and Tanzania with the goal of promoting the economic empowerment of women and young graduate women and improving food and nutrition security of their households.